The Managerial Strategies of School Principals in Enhancing Teacher Professionalism in Cluster I, Bangil District, Pasuruan Regency - Nasudi Nasudi; Taufiq Harris; M. Furqon Wahyudi (The Future of Education Journal, 2025)
This study aims to describe and analyze the managerial strategies of school principals in improving teacher professionalism in Cluster I, Bangil District, Pasuruan Regency, with research sites at UPT Educational Unit SDN Dermo I Bangil and UPT Educational Unit SDN Latek Bangil. This research uses a qualitative approach with a case study type. Data collection techniques were conducted through in-depth interviews, observations, and documentation studies. The research informants include school principals, teachers, and relevant parties within the school cluster environment. The results show that the managerial strategies of the school principals are implemented through the stages of planning, implementation, and evaluation of teacher professional development programs. Planning is carried out through the preparation of school and cluster programs, implementation is realized through KKG activities, academic supervision, as well as teacher training and mentoring, while evaluation is conducted through performance monitoring and joint reflection. Supporting factors include the commitment of the school principals, cooperation between schools within the cluster, and teacher motivation, while inhibiting factors include limited infrastructure, time constraints, and varying teacher competencies. The managerial strategies of the school principals have a positive impact on improving teachers' pedagogical, professional, social, and personal competencies. This study recommends strengthening cluster collaboration and data-driven planning as continuous efforts to improve teacher professionalism.